Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1007/s002230010010
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Bone Density, Quantitative Ultrasound, and Vertebral Fractures in Relation to Collagen Type I Alpha 1 Alleles in Elderly Women

Abstract: Previous studies have demonstrated that an Sp1 binding site polymorphism in the collagen type I gene (COLIA1) is related to reduced bone mineral density (BMD) and osteoporotic fractures in certain populations, particularly in the elderly. We have examined the relationship among these COLIA1 Sp1 alleles, BMD, quantitative ultrasound properties of bone, and fractures in a population-based cohort of elderly women from the UK. The study group comprised 314 women aged 75 years and over who agreed to participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
3
17
0
1
Order By: Relevance
“…This was very recently supported by the study of Kann et al, 25 which showed a negative association between COLIA1 Sp1 polymorphism and ultrasound transmission velocity in the calcaneus in postmenopausal women. However, in agreement with the study of Ashford et al, 32 we did not find an association between the ultrasound parameters and COLIA1 Sp1 polymorphism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was very recently supported by the study of Kann et al, 25 which showed a negative association between COLIA1 Sp1 polymorphism and ultrasound transmission velocity in the calcaneus in postmenopausal women. However, in agreement with the study of Ashford et al, 32 we did not find an association between the ultrasound parameters and COLIA1 Sp1 polymorphism.…”
Section: Discussionsupporting
confidence: 93%
“…19 21 23 26 27 However, other studies failed to show an association between the COLIA1 Sp1 binding site polymorphism and osteoporosis in postmenopausal women. [28][29][30][31][32] Thus, the association between the COLIA1 gene and osteoporosis is still not definitely established.…”
mentioning
confidence: 99%
“…29 The T allele of this SNP was reported to act as a risk factor to osteoporotic fracture in some studies, 12,14 but not in other populations. 30,31 We also analyzed the relationship between SNP2 and BMD in this population, and the risk effect of this SNP was not observed (Long J-R, personal communication). So far, only a few studies have been conducted to address the relationship between this SNP and bone geometry or bone structure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the COLIA1 Sp1 polymorphism has been found to play an important role in the pathogenesis of osteoporosis by affecting BMD and other predictors of osteoporotic fracture risk, such as ultrasound properties of bone and skeletal geometry. 28 A study by Mann et al 26 showed that the COLIA1 Sp1 polymorphism predisposed to osteoporotic fracture by affecting bone density and quality. The association between the COLIA1 genotype and increased femoral neck angle may contribute to the BMDindependent increase in hip fracture risk noted in previous studies of individuals who carry the 's' allele.…”
Section: G-r Ji M Yao C-y Sun Et Almentioning
confidence: 99%